LINKING KNOWLEDGE BASED ECONOMIC INDICATORS WITH FINANCIAL REPORTING QUALITY AN EMPIRICAL STUDY USING PANEL DATA ANALYSIS (World Economics and Finance Bulletin, 2026)
This study examines whether national knowledge assets improve banks financial reporting quality in four MENA economies Iraq, Saudi Arabia, Egypt, and the United Arab Emirates over 2010 2024